Factors causing students’ learning difficulties in Biology subject - Azhari, Sopian; Rizaldi, Dedi Riyan; Fahrurrozi, Muhammad; Nilwan, Nilwan; Ahyani, Nurul (Universitas Ahmad Dahlan, 2022)
This study aims to determine the factors that cause learning difficulties for class X MIPA students at Madrasah Aliyah Plus Nurul Islam Sekarbela. This research is a qualitative research. The subjects of this study were students of class X MIPA at MA Plus Nurul Islam Sekarbela. The sampling technique used random sampling with a sample of 22 students. The research data collection method uses an observation sheet in the form of a questionnaire. The data analysis technique uses descriptive qualitative with percentage categories. The results showed that in general the factors causing learning difficulties in class X MIPA students at MA Plus Nurul Islam Sekarbela consisted of internal factors including and physiology by 43% and psychology by 61%. While external factors include aspects of the family environment by 46%, school environment by 57%, and community environment by 66%.